Comparison of Forensics Death Investigation in Indonesia and Belgium - Rahmadani, Anindita Mutiara (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Forensic examination is crucial in obtaining evidence as soon as possible since the human body is a source of biological evidence that can change over time. There are differences between the systems and services provided by forensic medicine in various countries.Purposes of the Research: This study aims to analyze the comparison of forensic death investigations between Indonesia and Belgium.Methods of the Research: This research is normative, using a conceptual and comparative approach. The literature study method was used to collect data for this study, which was analyzed qualitatively.Results Main Findings of the Research: The analysis results show that the forensic examination system in Indonesia applies Scientific Crime Investigation (SCI). By using science and technology combined with criminal analysis, the police can solve criminal cases through the use of SCI methods. Meanwhile, the forensic investigation system in Belgium uses the Medical Examiner System, where a medical examiner is appointed to investigate the cause and manner of death in accordance with Belgian laws and regulations.